Uric acid transporter inhibitors for gout - Philip K. Tan; Jeffrey N. Miner (International Association of Physical Chemists (IAPC), 2017)
Gout is a common inflammatory arthritis that is caused by chronically-elevated serum uric acid (sUA) levels (hyperuricemia). In humans, sUA levels are predominantly controlled by a variety of transporters that mediate the elimination of uric acid through the kidneys and intestines, a process that is altered in most gout patients. In this review, we highlight our current understanding of uric acid handling in healthy individuals and gout patients, therapies for gout that target uric acid transporters, and the mechanism of other therapies that alter sUA levels through interactions with uric acid transporters.